Effect of intraurethral instillation of cooled versus room temperature lignocaine gel on pain perception during outpatient rigid cystoscopy - Singh, Ravinder; Paul R., Fredrick (International Surgery Journal, 2023)
Background: Reducing temperature of topically applied lignocaine gel for maximal anesthesia during cystoscopy in conscious patients have yielded mixed results. This prospective randomised controlled study was undertaken to compare pain mitigating effect of lignocaine gel at 4°C versus at room temperature during rigid cystoscopy in male patients. Methods: The study consists of 126 consecutive patients (n=126) who were randomly assigned into two groups: Group 1 (control, n1=63) received 2% topical lignocaine at room temperature, Group 2 (L4, n2=63) received topical lignocaine cooled to 4°C prior to insertion of rigid cystoscope. Pain during instillation of lignocaine and during performance of rigid cystoscopy was measured by independent evaluator on non-graphical 100-mm visual analogue scale (VAS). Results: Mean pain score for cystoscopy in L4 was lower (46.69±10.38) than that in CONTROL (49.19±12.47), this difference was statistically not significant (p value, one tail =0.11, >0.05). Mean pain score for instillation in L4 was 14.80±6.00 and that for control was higher at 17.04±6.54 with difference in pain scores being statistically significant (p value, one tail =0.02, <0.05). Conclusions: With regard to reducing pain perception during rigid cystoscopy, cooled lignocaine gel at 4°C has no benefit over room temperature lignocaine gel, however cooling lignocaine gel to 4ºC does significantly decrease pain of instillation of gel into urethra.